Proceedings of the 52nd Annual ACM SIGACT Symposium on Theory of Computing 2020
DOI: 10.1145/3357713.3384322
|View full text |Cite
|
Sign up to set email alerts
|

Classical algorithms, correlation decay, and complex zeros of partition functions of Quantum many-body systems

Abstract: We present a quasi-polynomial time classical algorithm that estimates the partition function of quantum many-body systems at temperatures above the thermal phase transition point. It is known that in the worst case, the same problem is NP-hard below this point. Together with our work, this shows that the transition in the phase of a quantum system is also accompanied by a transition in the hardness of approximation. We also show that in a system of n particles above the phase transition point, the correlation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 41 publications
(69 reference statements)
3
39
0
Order By: Relevance
“…Note added.-Regarding the classical simulations of quantum Gibbs states, we identified a related result obtained using a similar approach [100] at the same time of our submission.…”
Section: Fig 3 Effective Hamiltonianh L For the Reduced Densitymentioning
confidence: 83%
“…Note added.-Regarding the classical simulations of quantum Gibbs states, we identified a related result obtained using a similar approach [100] at the same time of our submission.…”
Section: Fig 3 Effective Hamiltonianh L For the Reduced Densitymentioning
confidence: 83%
“…Let Φ be a finite-range interaction on Z. If Φ satisfies uniform clustering with decay ε( ) in (24), then for every finite interval I ⊂ Z split into three subintervals I = ABC with |B| ≥ 2 ≥ 0 and every pair of observables Proof. We illustrate the proof of the first inequality, the other one is completely analogous.…”
Section: Proposition 71 (Local Indistinguishability)mentioning
confidence: 99%
“…Remarkably, Araki's result was extended for different correlation functions to higher dimensional systems above a threshold temperature in a series of papers [22,31,39,44], both for classical and quantum systems. In a recent work [24], the exponential decay of correlations property was related to the absence of complex zeroes of the partition function close to the real axis. Moreover, it is known that systems with a positive spectral gap exhibit exponential decay of correlations [29].…”
Section: Introductionmentioning
confidence: 99%
“…The framework of viewing partition functions as polynomials in the complex plane of the underlying parameters has been wellexplored in statistical physics and has recently gained traction in computer science as well in the context of approximate counting. On the positive side, zero-free regions in the complex plane translate into efficient algorithms for approximating the partition function (Barvinok 2017;Patel & Regts 2017) and this scheme has led to a broad range of new algorithms even for positive real values of the underlying parameters (Guo et al 2021(Guo et al , 2020Harrow et al 2020;Liu et al 2019;Liu et al 2019a,b;Peters & Regts 2018. On the negative side, the presence of zeros poses a barrier to this approach and, in fact, it has been demonstrated that zeros mark the onset of computational hardness for the approximability of the partition function (Bezáková et al 2020;Bezáková et al 2021;Goldberg & Guo 2017;Goldberg & Jerrum 2014).…”
Section: Introductionmentioning
confidence: 99%